Принципи діяльності Департаменту кіберполіції Національної поліції України: теоретико-правові аспекти - Береза, В. В.; Bereza, V. V.; ORCID: http://orcid.org/0000-0002-5931-2194 (Форум права. - 2017. - № 5. - С. 44–48, 2017)
Розглянуто енциклопедичні та наукові погляди на зміст правової категорії як «принципи». Наведено ключові ознаки досліджуваного терміну, враховуючи наявність серед вчених-правників значної кількості наукових позицій та неналежний стан висвітлення терміну «принципи» в рамках національного правового поля. Обґрунтовано поділ принципів діяльності Департаменту кіберполіції Національної поліції України на дві групи: загальні (міжгалузеві) та спеціальні (галузеві).

The author of the article has stated that one of the most important factors on the way of building a legal state is the counteraction to crimes aimed at e-government, e-banking, e-commerce and other high-tech industries. The need of timely and systemic response to modern hybrid challenges and threats caused by the influence of a complex of socio-demographic, economic, political, legal, psychological and technological factors has been determined. The author has provided the thesis that the issues of the principles of certain law enforcement agencies’ activity have repeatedly attracted the attention of a number of scholars within law area, but scientific research regarding the definition of the content of the principles of the studied law enforcement agency’s activity was not conducted because of the creation of the Cyberpolice Department of the National Police of Ukraine as a new executive agency, which legal regulation of its activity is at the stage of formation. In order to achieve the objective of this article, the author has studied encyclopedic and scientific points of view on the content of such a legal category as «principles». It has been concluded that there is the possibility of distinguishing such key features of the stated legal category as, first: principles according to their essence – are a generalized theoretical interpretation of the laws and patterns of objective development of certain public relations; – secondly, the principles are directly or indirectly reflected in the current legislation. The author has provided the list of key principles of the activities of the Cyberpolice Department of the National Police of Ukraine, taking into account the presence of a significant number of scientific points of view among scholars within law area and the lack of proper coverage of the term of «principles» within the framework of the national legal boundaries. The author has grounded the division of the principles of the activities of the Cyberpolice Department of the National Police of Ukraine into two groups: general (intersectorial), which, according to the author, include: the rule of law principle, the principle of observance of human rights and freedoms, the principle of legality and special (sectoral) ones, among which the following are defined: openness and transparency principle, the principle of political neutrality, the principle of interaction with the population on the partnership basis, the principle of continuity, the principles of international cooperation and the principles of extradition.

Рассмотрены энциклопедические и научные взгляды касательно содержания такой правовой категории как «принципы». Приведены ключевые признаки исследуемого термина, учитывая наличие среди ученых-юристов значительного количества научных позиций и ненадлежащее состояние освещения термина «принципы» в рамках национального правового поля. Обоснованно делание принципов деятельности Департамента киберполиции Национальной полиции Украины на две группы: общие (межотраслевые) и специальные (отраслевые).
Principles of the Department of Cyber Police of the National Police of Ukraine: Theoretical and Legal Aspects
Принципы деятельности Департамента киберполиции Национальной полиции Украины: теоретико-правовые аспекты
Береза, В. В. Принципи діяльності Департаменту кіберполіції Національної поліції України: теоретико-правові аспекти [Електронний ресурс] / В. В. Береза // Форум права. - 2017. - № 5. - С. 44–48. – Режим доступу: http://nbuv.gov.ua/j-pdf/FP_index.htm_2017_5_7.pdf.
Береза В. В. Принципи діяльності Департаменту кіберполіції Національної поліції України: теоретико-правові аспекти . Форум права: електрон. наук. фахове вид. 2017. № 5. С. 44–48. URL: http://nbuv.gov.ua/j-pdf/FP_index.htm_2017_5_7.pdf.
Береза В. В. "Принципи діяльності Департаменту кіберполіції Національної поліції України: теоретико-правові аспекти." Форум права 5 (2017): 44–48.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; Департаменту кіберполіції; Департамента киберполиции; Department of Cyber Police; діяльність; деятельность; activity; принципи діяльності; принципы деятельности